Listening of the oral extended expressions in the context of preschoolers’ speech development - Kharchenko, Nataliya (East European Journal of Psycholinguistics, 2014)
The paper is focused on the analysis of the researches by L. S. Vygotsky, A. V. Zaporozhets, D. B. Elkonin, N. S. Karpinskaya, L. A. Kalmykova, A. V. Leontiev,  V. S. Mukhina, A. I. Nikiforova, L. S. Slavina,  B. M. Teplov in the context of listening skills of preschool children. It has been proved that the problem of listening skills development in preschool children is closely related to the study of artistic-aesthetic perception features of literary texts and understanding the means of expressiveness by children along with the genesis of understanding extended utterances by preschoolers. Analysis of psychological, psycho-pedagogical, ontolinguistic and not numerous psycholinguistic researches showed potential of preschoolers to perceive and understand the extended utterances.ReferencesAranovskaya-Dubovis, D. M. (1955). Ponimanie skazki doshkol’nikom [Understanding of taleby a preschooler]. Doshkol’noe Vospitanie, 10, 33-40.Akhutina, T. V. (2002). Neirolingvisticheskiy analiz dinamicheskoj afazii. O mehanizmahpostroeniya vyskazyvaniya [Neurolinguistic analysis of dynamic aphasia. On the mechanisms ofbuilding the utterance]. Moscow: Terevinf.Bieva, E. G. (1984). Faktory, vlijajushhie na ponimanie tekstov (na materiale detskoj rechi)[Factors influencing understanding of texts (on the material of chil’s speech)]. Ph.D. thesis: 10.02.19.Moscow.Bodrova, E.V. (1981). Psihologicheskie aspekty ponimanija literaturnyh tekstov doshkol’nikami[Psychological aspects of understanding the literary texts]. Voprosy Psihologii, 5, 116-120.Vygotsky, L. S. (1991). Pedagogicheskaja psihologija [Pedagogical psychology]. Moscow:Pedagogika-Press.Vygotsky, L. S. (1986). Psihologija iskusstva [Psychology of art]. Moscow: Iskusstvo.Gurovich, L. M. (1973). Ponimanie obraza literaturnogo geroja det’mi starshego doshkol’nogovozrasta (6-7 let) [Understanding the image of a literary hero by children of a senior preschool age(6–7 years)]. Avtoref. dis. na soisk. uchenoj stepeni kand. ped. nauk. Moscow.Gurovich L. M., Beregovaya L.B., Loginova V.I. (1992). Rebyonok i Kniga [Child and a Book].S.-Petersburg.Eliseeva, M. B. (2008). Kniga v vosprijatii rebionka ot rozhdeniya do 7 let [Book in child’sperception from birth to 7 years]. Moscow: TC Sfera.Zaporozhets, A. V. (1986). Izbrannye psihologicheskie trudy [Selected psychological works]:V 2-h t. T. 1. Psihicheskoe razvitie rebjonka. Moscow: Pedagogika.Zaporozhets, A. V. (1948). Psihologija vosprijatija skazki rebjonkom-doshkol’nikom[Psychology of perception the tales by a preschooler]. Doshkol’noe Vospitanie, 9, 34-41.Kalmykova, L. O. (2008). Psihologіya formuvannia movlennєvoї dіjal’nostі dіtei doshkіl’nohovіku [Psychology of Forming Speech Activity of Preschool Children]. Kyiv: Fenіks.Karpinskaya, N. S. (1972). Hudozhestvennoe slovo v vospitanii detej [Literary word inchildren’s upbringing]. Moscow: Pedagogika.Kontseva, O. M. (1940). Rozumіnnja ditinoju bajki [Understanding the fable by a child ].Pracі Respublіkanskoyi Naukovoyi Konferencії z Pedagogіki і Psihologії. T.ІІ. Psihologіya. 135-145.Kruglyakova, T. A. (2006). Modifikacija stihotvornogo teksta v rechevoj dejatel’nosti rebjonka[Modification of expressed in verse text in speech activity of a child]: Ph.D. thesis: 10.02.19. S.-Petersburg.Leontyev, A. N. (1947). Psihologicheskie voprosy soznatel’nosti uchenija [Psychologicalquestions of conscious teaching]. Voprosy Psihologi Ponimanija. – Moscow: APN RSFSR. Vyp. 7.Lyublinskaya, A. A. (1965). Ocherki psihicheskogo razvitija rebjonka [Essays of child’smental development]. Moscow: Prosveshhenie.Malahova, A. D. (1981). Vzaimodejstvie obraznyh i verbal’nyh komponentov v processeponimanija [Interaction of imaginative and verbal components in the process of understanding].Voprosy psihologii, 5, 63-73.Morozova, N. G. (1947). O ponimanii teksta [On understanding the text]. Izvestija APNRSFSR. Vyp. 7: Voprosy Psihologii Ponimaniya, 191-240.Muhina, V. S. (1997) Vozrastnaja psihologija [Developmental Psychology]. Moscow.Nikiforova, O. I. (1969). Psihologicheskie voprosy vosprijatija hudozhestvennoj literatury[Psychological problems of belles-letters perception]. Doctor of Psychology thesis: 19.00.07.APNSSSR, NII psihologii. Moscow.Repina, T. A. (1959). Rol’ illustracii v ponimanii hudozhestvennogo teksta det’midoshkol’nogo vozrasta [Role of illustration in understanding of literary text by children of a preschoolage]. Voprosy Psihologii, 1, 127-140.Slavina, L. S. (1947). Ponimanie ustnogo rasskaza det’mi rannego vozrasta [Understanding oforal narration by the children of early age]. Izv. APN RSFSR, 7, 41-79.Teplov, B. M. (1947). Psihologicheskie voprosy hudozhestvennogo vospitanija [Psychologicalproblems of artistic upbringing]. Izvestija APN RSFSR, #. 11.Fliorina, E. A. (1961). Jesteticheskoe vospitanie doshkol’nikov [Aesthetic upbringing ofpreschoolers]. Moscow: APN RSFSR.Civanjuk, N. A. (1974). Nekotorye osobennosti vosprijatija skazki det’mi 3-4 let [Somefeatures of perception the tale by 3-4 years old children]. Doshkolnoye Vospitanie, 6, 41-45.Jel’konin, D. B. (2007). Detskaja psihologija [Psychology of a child]. B. D. Jel’konin, Ed. –Moscow: Akademiya.Jakovlicheva, A. F. (1953). Znachenie teksta i risunka, ih vzaimootnoshenij dlja ponimanijarebjonkom doshkol’nogo vozrasta detskoj knigi [The value of text and a picture, their interrelations forunderstanding by a child of a preschool age of a childish book. Ph.D. thesis]. Moscow.
Keywords: listening; perception of speech; understanding of speech; utterance; text; preschoolers.